Applying the Spatial Transmission Network to the Forecast of Infectious Diseases Across Multiple Regions - Wang, Huimin; Qiu, Jianqing; Li, Cheng; Wan, Hongli; Yang, Changhong; Zhang, Tao (Frontiers in Public Health, 2022)
Objective: Timely and accurate forecast of infectious diseases is essential for achieving precise prevention and control. A good forecasting method of infectious diseases should have the advantages of interpretability, feasibility and forecasting performance. Since previous research had illustrated that the spatial transmission network (STN) showed good interpretability and feasibility, this study further explored its forecasting performance for infectious diseases across multiple regions. Meanwhile, this study also showed whether the STN could overcome the challenges of model rationality and practical needs. Methods: The construction of STN framework involved three major steps: spatial kluster analysis by tree edge removal (SKATER) algorithm, structure learning by dynamic Bayesian network (DBN), and parameter learning by the vector autoregressive moving average (VARMA) model. Then we evaluated the forecasting performance of STN by comparing its accuracy with that of the mechanism model like SEIRS and machine learning algorithm like long-short term memory (LSTM). At the same time, we assessed the robustness of forecasting performance of STN in high and low incidence seasons respectively. The influenza-like illness (ILI) data in the Sichuan Province of China from 2010 to 2017 was used as an example for illustration. Results: The STN model revealed that ILI was likely to spread among multiple cities in Sichuan during the study period. During the whole study period, the forecasting accuracy of the STN (MAPE = 31.134) was significantly better than that of the LSTM (MAPE = 41.657) and the SEIRS (MAPE = 62.039). In addition, the forecasting performance of STN was also superior to those of the other two methods in either the high incidence season (MAPE = 24.742) or the low incidence season (MAPE = 26.209), and the superiority was more obvious in the high incidence season. Conclusion: This study applied the STN to the forecast of infectious diseases across multiple regions. The results illustrated that the STN not only had good accuracy in forecasting performance, but also indicated the spreading directions of infectious diseases among multiple regions to a certain extent. Therefore, the STN is a promising candidate to improve the surveillance work.